2017
DOI: 10.3758/s13423-017-1277-9
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the recent visual past: Hierarchical knowledge-based effects in visual working memory

Abstract: This paper presents two experiments that examine the influence of multiple levels of knowledge on visual working memory (VWM). Experiment 1 focused on memory for faces. Faces were selected from continua that were constructed by morphing two face photographs in 100 steps; half of the continua morphed a famous face into an unfamiliar one, while the other half used two unfamiliar faces. Participants studied six sequentially presented faces each from a different continuum, and at test they had to locate one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This degrading-reemerging trend was evident in previous works for the correlation between neural population coding of neighboring vibration frequencies (Barak et al, 2010); for the accuracy of stimulus decoding via dynamic coding subspaces (Murray et al, 2017); and for the correlation between the gaze pattern and the stimulus geometry (Linde-Domingo & Spitzer, 2023). This reconstructive view of WM is in line with the studies investigating response biases in visual WM (Poirier et al, 2017; Scotti et al, 2021) and coincides with the notion of reconstructive memory in general (Roediger & DeSoto, 2015; Xue, 2022). During reconstruction, sensed information integrates with internal knowledge, rendering subjective, rather than objective, representations, and occasionally leads to false memory (Mendez & Fras, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…This degrading-reemerging trend was evident in previous works for the correlation between neural population coding of neighboring vibration frequencies (Barak et al, 2010); for the accuracy of stimulus decoding via dynamic coding subspaces (Murray et al, 2017); and for the correlation between the gaze pattern and the stimulus geometry (Linde-Domingo & Spitzer, 2023). This reconstructive view of WM is in line with the studies investigating response biases in visual WM (Poirier et al, 2017; Scotti et al, 2021) and coincides with the notion of reconstructive memory in general (Roediger & DeSoto, 2015; Xue, 2022). During reconstruction, sensed information integrates with internal knowledge, rendering subjective, rather than objective, representations, and occasionally leads to false memory (Mendez & Fras, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Other studies, however, suggest older workers are commonly considered less qualified for management positions (e.g., Cheung & Woo, 2021) or found that such positions are rated as equally accessible for younger and older workers (Derous & Decoster, 2017). The stereotypicality bias in speaker recall and speaker ratings are consistent with biases in memory performance for object pictures (Hemmer & Steyvers, 2009;Huttenlocher et al, 2000;Poirier et al, 2017). These studies also show that recall performance for a stimulus dimension, such as picture size, is biased toward the category average, where the average can be based on the items that are shown during the experiment and on the prior knowledge of the participants.…”
Section: Discussionmentioning
confidence: 69%
“…A second way in which stereotypicality may contribute to errors is by influencing guessing for the speaker category (Ehrenberg & Klauer, 2005; Klauer & Ehrenberg, 2005; Wegener & Klauer, 2004). In that case, people use prior knowledge to fill gaps in their memory for the specific study items (Hemmer & Steyvers, 2009; Huttenlocher et al, 2000; Poirier et al, 2017). In fact, guessing biases might completely explain better memory performance for stereotypical information in some paradigms (Hicks & Cockman, 2003; Schaper et al, 2019; Sherman & Bessenoff, 1999).…”
Section: Age Categorization and Stereotyping At Workmentioning
confidence: 99%
“…According to Strempler-Rubio, Alvarado and Vila [62], EM develops late and deteriorates early, being more vulnerable to neuronal dysfunction than other memory systems. In addition, existing studies on EM refer to the imprecision of this type of memory [63]. This is due to the fact that the person reconstructs images and facts in a subjective way, and the reconstructed version can vary from the original.…”
Section: The Episodic Memorymentioning
confidence: 99%